2017
DOI: 10.1016/j.scitotenv.2016.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of abuse and their metabolites in the urban rivers of Beijing, China: Occurrence, distribution, and potential environmental risk

Abstract: The occurrence and distribution of five drugs of abuse and their metabolites, namely, methamphetamine (METH), amphetamine (AMP), ketamine (KET), ephedrine (EPH), and hydroxylimine (HY), were investigated in the surface water in urban rivers in Beijing, China. A total of 117 surface water samples were collected from the seven rivers in the Beijing urban areas during four different seasons. Laboratory analyses revealed that EPH and METH were the most predominant drugs, with detection frequency ranging from 94% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 61 publications
1
28
1
1
Order By: Relevance
“…Concentrations of MET in the influent were in the range of ≤ LOD-1.24 ng/L and in the effluent for ≤ LOD-0.18 ng/L. In this study, the concentrations of MET were lower than the reported levels in other countries, such as the US (62 ng/L) [9], Croatia (94 ng/L) [12] and Belgium (16 ng/L) [10].…”
Section: Concentration and Frequency Of Detection Of The Target Illiccontrasting
confidence: 62%
See 3 more Smart Citations
“…Concentrations of MET in the influent were in the range of ≤ LOD-1.24 ng/L and in the effluent for ≤ LOD-0.18 ng/L. In this study, the concentrations of MET were lower than the reported levels in other countries, such as the US (62 ng/L) [9], Croatia (94 ng/L) [12] and Belgium (16 ng/L) [10].…”
Section: Concentration and Frequency Of Detection Of The Target Illiccontrasting
confidence: 62%
“…High METH loads were found in XBQ-1 (20.65 mg/d/1000 inh) and XBQ-3 (18.99 mg/d/1000 inh). These loads were lower than those of wastewater samples (1500-1800 mg/d/1000 inh) in Australia [6] and other cities in China such as Haerbin (181.20 ± 6.50 mg/d/1000 inh) [8], Yinchuan (148.00 ± 145.20 mg/d/1000 inh) [8,12], and the mean METH load in WWTPs from 18 cities in China was 67.80 ± 45.2 mg/d/1000 inh, which was threefold higher than the mean load in this study [8].…”
Section: Mean Loads Of Illicit Drugsmentioning
confidence: 67%
See 2 more Smart Citations
“…A 2015 szeptemberétől 2016 júliusáig négy ütemben, évszakonként egyszer megismételt vizsgálat alapján a mintákban található drogmennyiség 49-92 százalékával az efedrin tekinthető domináns szernek, amely azonban egyszersmind az asztma és a hörghurut kezelésére alkalmazott hagyományos kínai gyógyászati termékek legális hatóanyaga is. A szintén jelentős mennyiségben előforduló metamfetamin és ketamin koncentrációja a belváros körzetében a legnagyobb (Zhang et al [2017]). …”
Section: áZsiaunclassified